The assessment of the variation of physico-chemical sources for drinking water quality using chemometrics: A case study at water treatment plants in Klang Valley - Rwoo, M.A.; Juahir, H.; Roslan, N.M.; Toriman, M.E.; Endut, A.; Azid, A.; Che Hasnam, C.N.; Mohd Saudi, A.S.; Kamarudin, M.K.A.; Rwoo, S.A.; Mustafa, A.D. (Penerbit UTM Press, 2016)
This case study characterizes the drinking water quality by using the multivariate technique. The spatial variation of the physico-chemical and heavy metals parameters toxicity with the drinking water quality based on 28 water treatment plants in Selangor, Malaysia from 2009 to 2012 was evaluated. The objectives of this study are to analyze the physio-chemical activities and heavy metals activities in the collected drinking water samples from the treatment plants, and to detect the source of pollution for the most revealing parameters. The discriminant analysis (DA) and the principal component analysis (PCA) are the chemometric techniques used to investigate the spatial variation of the most significant physico-chemical and heavy metal parameters of the drinking water samples. The classification matrix accuracy for standard mode of DA, forward stepwise and backward stepwise for the physico-chemical and heavy metal parameters are excellent. PCA highlighted 13 significant parameters out of 18 physico-chemical water quality parameters and 14 significant parameters out of 16 heavy metal parameters. PCA was carried out to identify the origin and source of pollution of each water quality parameters. For that reason, this study proves that chemometric method is the principle way to explain the characteristic of the drinking water quality.